Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
We will solve the following equation for h.
[tex]\begin{gathered} 3(5-h)-2(h-2)=-1 \\ \\ 15-3h-2h+4=-1 \\ \\ -5h+19=-1 \end{gathered}[/tex]Where first we make the multiplications, and then we group the similar terms, let's continue
[tex]\begin{gathered} -5h+19=-1 \\ \\ -5h=-19-1 \end{gathered}[/tex]In the last line, we pass the 19 that was on the left with the opposite sign on the right side of the equation. Continuing the calculation
[tex]\begin{gathered} -5h=-20 \\ \\ 5h=20 \end{gathered}[/tex]
where in that last line, we multiplied both sides by the signal minus . Let us finish
[tex]\begin{gathered} 5h=20 \\ \\ h=\frac{20}{5} \\ \\ h=4 \end{gathered}[/tex]We conclude that the value of h, that solves this equation is h=4.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.